PERCERAIAN YANG DISEBABKAN SALAH SATU PASANGAN PINDAH AGAMA DI PENGADILAN NEGERI BANDUNG - Wiwin Putra, Joni Zulhendra dan (Normative Jurnal Ilmiah Hukum, 2024)
Marriage cannot be separated from the religious aspect, especially when the Marriage Law emphasizes the importance of the religious aspect in the conditions for the validity of a marriage as regulated in Article 2 paragraph (1) "Marriage is valid, if it is carried out according to the laws of each respective religion and belief", it was emphasized by MUI fatwa Number 4/MUNAS/VII/- MUI/8/2005 that Muslim women are prohibited from marrying non-Muslim men or Muslim men are prohibited from marrying women from people of the book, in the Bandung District Court Decision Number: 87/Pdt. G/2020/PN.Bdg, there was a divorce case that was caused by one of the parties changing religion. The Judge's Consideration of Divorce Caused by One of the Spouses Changing Religion at the Bandung District Court (Study of Bandung District Court Decision Number: 87/Pdt.G/2020/PN.Bdg) is in the case where the Plaintiff has converted to Islam and insists on filing for divorce on the grounds that his new religion didn't allow it. In accordance with the Fatwa of the Indonesian Ulema Council Number 4/MUNAS VII/MUI/8/2005 concerning interfaith marriages, it is stipulated that interfaith marriages are haram and invalid. This is also based on the provisions of Article 19 of Government Regulation no. 9 of 1975 concerning the Implementation of Law Number 1 of 1974 concerning Marriage and the frequent occurrence of continuous disputes, quarrels and fights due to differences of opinion and belief, the Legal Consequences of Divorce Caused by One of the Couples Changing Religions are the most important regarding the division of joint assets, maintenance and maintenance for the survival of their children, regarding child custody (hadhanah) and the settlement of their marital assets is resolved separately from the divorce suit they filed. The process of settling marital assets due to divorce is carried out according to the respective laws as intended in Article 37 of Law Number 1 of 1974 concerning Marriage.